Effects of phosphate-solubilizing bacteria application on soil phosphorus availability in coal mining subsidence area in Shanxi. Issue 1 (1st January 2017) - Shi, Xiao-Kai; Ma, Juan-Juan; Liu, Li-Jun
ABSTRACT: The effect of phosphate-solubilizing bacteria (PSB) application on phosphorus (P) availability in reclaimed soil in coal mining subsidence region was investigated. Seven treatments were carried out including control, chicken manure (CM), PSB, PSB + tricalcium phosphate (TCP), CM + TCP, PSB + ground phosphate rock (GPR) and CM + GPR. The results showed soil Olsen-P concentration and phosphatase level as well as the yield of pakchoi ( Brassica chinensis L.) were significantly higher in PSB application treatments compared to the corresponding CM application treatments. Soil phosphatase, invertase and urease contents were increased most significantly in PSB treatment, 1.18-, 1.31- and 2.32-fold higher than those in the control, respectively. Soil Ca2 -P, Ca8 -P, Fe-P and Al-P concentrations exhibited the greatest increases in PSB + TCP treatment, while occluded-P showed minor changes in different treatments. Application of PSB fertilizer reduced the transformation of Olsen-P to Ca10 -P, thus increasing P availability in reclaimed soil of coal mining subsidence area.